Serum Vitamin D Levels in Relation to Abdominal Obesity in Children and Adolescents: A Systematic Review and Dose-Response Meta-Analysis - Hajhashemy, Zahra; Lotfi, Keyhan; Heidari, Zahra; Saneei, Parvane (Frontiers in Nutrition, 2022)
Background: Findings of epidemiological studies that investigated the relation between serum vitamin D levels and abdominal obesity were inconsistent. To evaluate the relationship between blood vitamin D levels and abdominal obesity in children and adolescents, we did a comprehensive review and dose-response meta-analysis. Methods: A comprehensive search in electronic databases including Scopus, Web of Science (ISI), MEDLINE (Pubmed), EMBASE and Google Scholar was conducted, up to May 2021, for epidemiological studies that investigated the linkage between serum vitamin D levels (as the exposure) and abdominal obesity (as the outcome) in children and adolescents. Results: Combining 19 effect sizes from 14 cross-sectional studies included 29,353 apparently healthy children illustrated that highest vs. lowest level of serum vitamin D was related to a 35% reduced odds of abdominal obesity (OR: 0.65; 95%CI: 0.50, 0.84). Linear dose-response analysis revealed that each 10 ng/mL increase in serum vitamin D levels was related to a 7% decrease in odds of abdominal obesity (OR: 0.93; 95%CI: 0.90, 0.95), only among investigations that used percentiles of waist circumference (> 75th or 90th) to define the disorder (including 6,868 total subjects and 1,075 cases with abdominal obesity). Increasing serum vitamin D levels from 20 to 40 ng/mL was related to reduce odds of abdominal obesity in children. Conclusion: A negative relationship between blood vitamin D levels and abdominal obesity in children and adolescents was discovered in this meta-analysis of epidemiologic studies. Among investigations that used waist circumference percentiles to define the disorder, the relationship was in a dose-response manner. To affirm this relationship, more researches are needed, particularly using prospective design.